Drivers of portfolio flows into Chinese debt securities amidst China's bond market development - Tuuli McCully (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2023)
The paper focuses on China's onshore bond market and the drivers of non-resident net portfolio flows into Chinese debt securities. Building on a theoretical model of push and pull factors as a foundation for the empirical analysis on drivers of bond flows into China, static and time-varying models are estimated to explain the importance of various push and pull factors in the context of China's bond market development. While China-specific pull factors, such as domestic economic growth prospects and asset returns, are important drivers of bond flows, the results reveal that global push factors, such as US interest rates and investor risk aversion, have recently gained significance as drivers of flows into China. This shift goes hand in hand with China's gradual bond market liberalization measures. The findings confirm China's continued bond market deepening and integration with the rest of the world.
urn:nbn:fi-fe20231205151484
Keywords: F32; F34; F36; F41; G11; G28; 330; capital flows; portfolio flows; push factors; pull factors; financial openness